The Odessa period of academic of AUAS A.O. Sapegin life: the prerevolutionary years (1903-1917) - Apostol, M. V. (History of science and technology, 2014)
The article investigates the prerevolutionary years of the Odessaperiod life ofacademicof AUAS A.O. Sapegin. It is provedthat it is theseyearswerea period of formationfor Sapeginas a scientist andorganizer.